The Discourse On Islam And Development: Western And Muslim Scholars’ Opinions - Budiman, Mochammad Arif (P3M Politeknik Negeri Banjarmasin, 2016)
There is ongoing debate among scholars concerning the relation between Islam and development. The focus of the debate is particularly about the compatibility issue. Western and Muslim scholars have their own stance and argumentation. While the former have accused Islam as an obstacle to development, the latter have assured that Islam is essentially compatible to development. Based on the Qur’anic point of view, it is obvious that religion and development are essentially related in a positive, direct and causal manner.